TEKNOLOGI PENGEMASAN UNTUK MENINGKATKAN PEMASARAN PRODUK LOKAL MADU KELULUD DUSUN LIMBUNG BANGKA - Khodijah, Nyayu Siti; Agustina, Fournita; Ginting, Mayarani (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Real work learning (KKN) is an academic obligation that must provide benefits for learning for students and provide solutions to problems in society in the form of smart creative ideas that are appropriate for the times. The socialization program for the right packaging technology to increase the marketing of superior products from Limbung, Jada Bahrin Village via online to creative business actors as part of the XV KKN_UBB Program with the theme